Seroprevalence of Plasmodium vivax in the Republic of Korea (2003-2005) using Indirect Fluorescent Antibody Test - Kim, Tong-Soo (The Korean Society for Parasitology and Tropical Medicine, 2014)
Plasmodium vivax reemerged in the Republic of Korea (ROK) in 1993, and is likely to continue to affect public health. The purpose of this study was to measure levels of anti-P. vivax antibodies using indirect fluorescent antibody test (IFAT) in border areas of ROK, to determine the seroprevalence of malaria (2003-2005) and to plan effective control strategies. Blood samples of the inhabitants in Gimpo-si, Paju-si, and Yeoncheon-gun (Gyeonggi-do), and Cheorwon-gun (Gangwon-do) were collected and kept in Korea Centers for Disease Control and Prevention (KCDC). Out of a total of 1,774 serum samples tested, the overall seropositivity was 0.94% (n=17). The seropositivity was the highest in Paju-si (1.9%, 7/372), followed by Gimpo-si (1.4%, 6/425), Yeoncheon-gun (0.67%, 3/451), and Cheorwon-gun (0.19%, 1/526). The annual parasite incidence (API) in these areas gradually decreased from 2003 to 2005 (1.69, 1.09, and 0.80 in 2003, 2004, and 2005, respectively). The highest API was found in Yeoncheon-gun, followed by Cheorwon-gun, Paju-si, and Gimpo-si. The API ranking in these areas did not change over the 3 years. The seropositivity of Gimpo-si showed a strong linear relationship with the API of 2005 (r=0.9983, P=0.036). Seropositivity data obtained using IFAT may be useful for understanding malaria prevalence of relevant years, predicting future transmission of malaria, and for establishing and evaluating malaria control programs in affected areas.